Jesus is ons versoening: die implikasies van die versoening vir die sending - Verster, P (Nederduitse Gereformeerde Teologiese Tydskrif, 2015)
This article gives an overview of the continuing debate on reconciliation, especially from the perspective of Paul. The author argues that different ways of perceiving reconciliation emerge from relevant literature. On the one hand, reconciliation is described as Christ’s representation, which has nothing to do with Old Testament sacrifice and substitution. Reconciliation with God is obtained by following Christ. Another possibility is that Christ is our reconciliation by substitution. The author reviews the implications for mission of this last perspective.